Traumas de la infancia de una niña de 11 años del sector Rincón de Cuba del cantón Baba - Sánchez González, Angi Isabel (2021)
This case study is an essential requirement of the students of the Technical University of Babahoyo of the Clinical Psychology career to obtain the title of Clinical Psychologist. The objective is to determine the incidence of childhood traumas in the behavior of an 11-year-old girl from the “Rincon de Cuba” sector of the Baba Canton. From the issue raised, it can be contextualized that a childhood trauma is a painful event that marks the life of an infant, causes many difficulties in different areas of life, be it social, academic and in this case in the family environment, since the loss of a loved one, mistreatment and rejection by family members, living in an environment where there is no tools and materials necessary for their studies and entertainment; causes the patient to demonstrate defiant and rebellious behavior. To deepen the investigation, several sessions were held, on different dates, in which the patient showed different behaviors, at the beginning of the first session she showed apathetic behavior, after the following sessions she showed a collaborative posture. The intervention that was carried out was by means of different psychological techniques, the clinical history and direct observation were used for the compilation of information, the "Esperi" test was applied and according to the ICD-10, a diagnosis was made in which the disease was detected. F91. 3 “Challenging and Oppositional Dissocial Disorder”, the prognosis of the treated case is favorable because the patient wishes to work on her behavior, therefore, we worked from cognitive behavioral therapy, this being the appropriate therapy to treat the discomfort that the patient presents.